2018
DOI: 10.1007/s11242-018-1009-2
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis and Horizontal Redistribution in Porous Media

Abstract: It is well known that multiphase flow in porous media exhibits hysteretic behaviour. This is caused by different fluid-fluid behaviour if the flux reverses. For example, for flow of water in unsaturated soils the process of imbibition and drainage behaves differently. In this paper we study a new model for hysteresis that extends the current playtype hysteresis model in which the scanning curves between drainage and imbibition are vertical. In our approach the scanning curves are non-vertical and can be constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 32 publications
0
38
0
Order By: Relevance
“…8, 9, 11, 12, 27. It has a physical basis 4,28 and it can be extended to depict the realistic cases accurately 24 . A similar hysteretic behavior is observed for the relative permeabilities too, although to a lesser extent.…”
Section: Introductionmentioning
confidence: 60%
See 3 more Smart Citations
“…8, 9, 11, 12, 27. It has a physical basis 4,28 and it can be extended to depict the realistic cases accurately 24 . A similar hysteretic behavior is observed for the relative permeabilities too, although to a lesser extent.…”
Section: Introductionmentioning
confidence: 60%
“…An extension describing nonvertical scanning curves is discussed in Ref. 24 and chapters 3,11 of Ref. 27.…”
Section: Mathematical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper we consider, in addition to (1.4), an extension of play-type hysteresis by introducing non-vertical scanning curves. It is achieved by adapting (1.4) in the following way (for small ε > 0) Such an extension was proposed in [6] and similar models were studied in [1,17]. In [6] it is shown that the model is consistent if ε satisfies certain upper bounds.…”
Section: Introductionmentioning
confidence: 99%